Gravity observations on Santorini island (Greece): Historical and recent campaigns - PARASKEVAS, Melissinos; PARADISSIS, Demitris; RAPTAKIS, Konstantinos; NOMIKOU, Paraskevi; HOOFT, Emilie; BEJELOU, Konstantina (Contributions to Geophysics and Geodesy, 2021)
Santorini is located in the central part of the Hellenic Volcanic Arc (South Aegean Sea) and is well known for the Late-Bronze-Age “Minoan” eruption that may have been responsible for the decline of the great Minoan civilization on the island of Crete. To use gravity to probe the internal structure of the volcano and to determine whether there are temporal variations in gravity due to near surface changes, we construct two gravity maps. Dionysos Satellite Observatory (DSO) of the National Technical University of Athens (NTUA) carried out terrestrial gravity measurements in December 2012 and in September 2014 at selected locations on Thera, Nea Kameni, Palea Kameni, Therasia, Aspronisi and Christiana islands. Absolute gravity values were calculated using raw gravity data at every station for all datasets. The results were compared with gravity measurements performed in July 1976 by DSO/NTUA and absolute gravity values derived from the Hellenic Military Geographical Service (HMGS) and other sources. Marine gravity data that were collected during the PROTEUS project in November and December 2015 fill between the land gravity datasets. An appropriate Digital Elevation Model (DEM) with topographic and bathymetric data was also produced. Finally, based on the two combined datasets (one for 2012–2014 and one for the 1970s), Free air and complete Bouguer gravity anomaly maps were produced following the appropriate data corrections and reductions. The pattern of complete Bouguer gravity anomaly maps was consistent with seismological results within the caldera. Finally from the comparison of the measurements made at the same place, we found that, within the caldera, the inner process of the volcano is ongoing both before, and after, the unrest period of 2011–2012.